Subjecthood of Quirky Subjects and GF-Split - Miechowicz-Mathiasen, Katarzyna (Wydawnictwa Szkolne i Pedagogiczne, 2005)
In this paper we show that most of the adduced intuitions about subjects and subjecthood are true for Nominative subjects and depend exactly on this Case, i.e. a subject is bound to have all, or most, of the subject properties only when it stands in Nominative. The problems with subjecthood properties arise, however, once the potential subject does not bear this apparently special Case, but is inherently Dative or Accusative, i.e. "Quirky". We argue that Quirky Subjects undeniably bear subjecthood and we support this view with relevant data. We also propose parameter settings for the analysed languages and eventually a definition of subject based on Ura's (2000) analysis of Grammatical Function Split phenomena (hence GF-Split).